Islamic Legal Thought Implementation in Indonesia - Ahmad Mathar; Hardianti Hardianti; Misbahuddin Misbahuddin; Kurniati Kurniati (Syntax Corporation Indonesia, 2022)
Islamic law is a system of law derived from the Qur'an and hadith, which subsequently evolved from legal philosophy. The result of legal thought is the production of legal documents based on the requirements of the community. In Indonesia, Islamic law grows and evolves in the form of four products of legal thought: fiqh, ulama fatwas, court rulings (jurisprudence), and laws. In Indonesia, the four products of legal thinking serve as rules for Muslims in national, state, and social life. This study sought to identify the outcomes of Islamic legal thinking in Indonesia. The technique employed is qualitative. According to the findings of this study, Islamic legal thought in Indonesia is comprised of the products of fiqh thought, fatwa thought, court decision thinking (jurisprudence), and legal thought. This product of Islamic legal philosophy touches on the order of Islamic society and, despite being independent of sharia law, can serve as a firm legal foundation.